2019
DOI: 10.1155/2019/6198495
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End-Products and Hyperglycemia Increase Angiopoietin-2 Production by Impairing Angiopoietin-1-Tie-2 System

Abstract: The angiopoietin-Tie-2 system plays a crucial role in the maintenance of endothelial integrity. Hyperglycemia and advanced glycation end-products (AGEs) are involved in endothelial cell dysfunction responsible of the pathogenesis of microvascular complications of diabetes. Here, we investigated whether glycated serum (GS) or hyperglycemia (HG) affect the angiopoietin-Tie-2 system in the microvascular endothelial cells HMEC-1. We found that culture for 5 days in the presence of AGEs and HG (alone or in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Ang-1 is an oligomeric glycoprotein that binds to and signals through Tie-2 ( 32 ), thereby enhancing vascular stability and modulating associated permeability. Ang-1 binding to Tie-2 induces intracellular signaling that regulates endothelial cell survival, migration, and permeability ( 33 ). In contrast, Ang-2 functions as an antagonist that prevents Ang-1-induced Tie-2 phosphorylation, driving extensive angiogenesis and vascular destabilization ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ang-1 is an oligomeric glycoprotein that binds to and signals through Tie-2 ( 32 ), thereby enhancing vascular stability and modulating associated permeability. Ang-1 binding to Tie-2 induces intracellular signaling that regulates endothelial cell survival, migration, and permeability ( 33 ). In contrast, Ang-2 functions as an antagonist that prevents Ang-1-induced Tie-2 phosphorylation, driving extensive angiogenesis and vascular destabilization ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The senescence induced by ageing and diabetes can disrupt the endothelial function because of reactive oxygen species (ROS), inflammatory mediators or inducible nitric oxide (iNO) [ 4 ]. The dysfunctional metabolism of endothelial cells produces advanced glycation end products (AGEs) that through their receptors (RAGEs) activate mitogen-activated protein kinase (MAPK) and NFκB cascades and increase the production of ROS [ 84 ], inflammatory (vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1) and monocyte chemoattractant protein-1 (MCP-1)) [ 85 ], profibrotic (matrix metalloproteinase (MMP)-2 protein) and prothrombotic factors (von Willebrand, plasminogen activator inhibitor-1 (PAI-1) and tissue factor (TF)) [ 86 ]. They are contributors to arterial stiffness, vascular calcification, and plaque accumulation in atherosclerosis-prone vessels and, consequently, diabetes mellitus-related vascular complications [ 87 ].…”
Section: Physiopathological Mechanismsmentioning
confidence: 99%
“… 88 Abnormal accumulation of AGEs occurs in the presence of persistent hyperglycemia. 89 The study by Dehnad et al. reported that continued exposure to AGEs in the liver led to an imbalance between AGEs clearance receptor (AGER1) and receptor for AGEs (RAGE), consequently resulting in excessive redox, inflammatory, and fibrogenic activity in NASH, which is mediated by NADPH oxidase 4 in hepatocytes.…”
Section: The Application Of Aav-mediated Gene Delivery System In Live...mentioning
confidence: 99%